Peran Kepemimpinan Dan Penerapan Manajemen Perubahan Dalam Peningkatan Daya Saing Organisasi di Universitas Islam Negeri Sumatera Utara - Grace Amalia Tondang; Nuri Aslami (Universitas Labuhanbatu, 2022)
The role of leadership in every organization is very important in developing change management and organizational competitiveness in universities in North Sumatra. The purpose of this paper is to conduct a deeper study of what factors affect competitiveness in North Sumatra universities both in terms of leadership and change management. The research method used is the Literature Review method (library study). The results of the study show that the role of leadership is very dominant in the sustainability and progress of higher education in North Sumatra. The strength of competitiveness is a driver to get the results of the competition (Competition Result) as expected, both in terms of the adequacy of the quality and quantity of students and a good image in the eyes of the community.